Evaluating alternatives to zinc oxide or antibiotics in nursery pig diets - Tingler, Hannah L.R.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
There has been an increase in consumer pressure to reduce the use of ZnO and antimicrobials in swine diets. Since there is limited research evaluating alternatives on nursery pig growth performance to replace antibiotics or ZnO. This study was conducted to test the dietary effects of ZnO, carbadox, and medium chain fatty acids (MCFA). The experiment used 360 (DNA 200x400, initially 5.4 ± 0.06 kg BW) nursery pigs weaned at 21d. At weaning, the pens were assigned to treatment in a complete randomized design containing 10 pens of treatments and 6 pigs/pen. The six dietary treatments included 1.) negative control, 2.) 3,000ppm ZnO phase 1; 1,500ppm ZnO phase 2, 3.) 50g/ton carbadox, 4.) 1% blend of C6:C8:C10, 5.) 1% feed energy R2 (Feed Energy Corp, Des Moines, IA) and 6.) 1% Formi GML (ADDCON, Bitterfeld-Wolfen, Germany). Pigs and feeders were weighed weekly to determine ADG, ADFI, and G:F in Phase 1 (0 to 7), Phase 2 (8 to 19), a common diet was fed from d 20 to 35d of the experiment. Data was analyzed using the SAS GLIMMIX (SAS version 9.4, Cary, NC) program with P<0.05. From d 0 to 19, pens fed ZnO or carbadox had improved (P<0.05) ADG compared to MCFA. These pens had an increased ADFI using ZnO or carbadox compared to the control, MCFA, and 1% Formi (P<0.0004). During the common phase diet there was no significant differences (P>0.05) for ADG, ADFI, or G:F. These results suggest that more research is needed to determine whether MCFA based products can replace ZnO or carbadox with little overall effect.
Keywords: Spring 2019